Open Educational Resource (OER):C-Programming Handout based Lab Session using MOODLE for Engineering Education - Dol, Sunita M.; Indi, Trupti S. (Journal of Engineering Education Transformations, 2025)
Open educational resources (OER) are free and openly licensed educational materials. It can be used for teaching, learning, research work and other purposes. OECD (Organization for Economic Co-operation and Development) defines this OER as "digitised materials offered freely and openly for educators, students, and selflearners to use and reuse for teaching, learning, and research. OER includes learning content, software tools to develop, use, and distribute content, and implementation resources such as open licences." Types of open educational resources include: full courses, course materials, modules, learning objects, open textbooks, openly licensed videos, tests, software, and other tools, materials etc. OER may be freely and openly available static resources and dynamic resources. We have developed "Open Education Resource (OER): CProgramming Handout based Lab Session using MOODLE". It consists of C-Programming Lab handouts for First Year Engineering students which contains the useful guidelines for implementing the program problem statements in the lab session. Practise problem statements are given in the each handout. Students practise those problem statements in lab session and submit on the MOODLE for assessment purpose. At the end of each lab session, the quiz will conducted on the MOODLE on the topic covered in the lab session. Since this OER is related to the C-Programming, any faculty or students from any stream can use this OER. We are going to use this OER for the students of First Year Engineering Program for CProgramming course in Semester II.